PENGARUH JENIS DAN KONSENTRASI BAHAN PENJERNIH TERHADAP KARAKTERISTIK CUKA KAKAO - Alit Arcana, Ida Bagus; Wartini, Ni Made; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
ABSTRACT Byproducts of fermented cocoa beans can be processed into cocoa vinegar. Cocoa vinegar produced is still cloudy, so it needs to be clarified. This study aims to determine the effect of type and concentration of fining agent on the characteristics of cocoa vinegar and to determine the type and concentration of the best fining agents to clarified cocoa vinegar. This study used a factorial Randomized Block Design consisting of 2 factors. First factor  is a type of fining agent consisting of bentonite, chitosan and gelatin, and second factor is a concentration of fining agent consisting of 0.5, 1, 1.5, 2, 2.5 ppm. Treatments are grouped into 2 groups to obtain 30 experimental units. The variables observed were clarity, pH, total dissolved solids, total acid, and acetic acid levels. The results showed that the type and concentration of purifying agents had an effect on the characteristics clarity, total dissolved solid, degree of acidity (pH), total acid, and acetic acid level of cocoa vinegar. The best treatment to clarify cocoa vinegar is the treatment of chitosan digesters with a concentration of 2 ppm, which produces cocoa vinegar with characteristics of clarity of 0.46 A; total dissolved solids of 2.90 o Brix, degree of acidity (pH) of 4.11; total acid of 0.33 mEq NaOH/g, and acetic acid level of 1.96% w/w. Keywords: Cocoa, vinegar, fining, bentonite, chitosan, gelatin